High performance rotation architectures based on the radix-4 CORDIC algorithm - Antelo, E.; Villalba, J.; Bruguera, J.D.; Zapata, E.L. (IEEE transactions on computers, 1997)
Traditionally, CORDIC algorithms have employed radix-2 in the first n/2 microrotations (n is the precision in bits) in order to preserve a constant scale factor. The authors present a full radix-4 CORDIC algorithm in rotation mode and circular coordinates and its corresponding selection function, and propose an efficient technique for the compensation of the nonconstant scale factor. Three radix-4 CORDIC architectures are implemented: 1) a word serial architecture based on the zero skipping technique, 2) a pipelined architecture, and 3) an application specific architecture (the angles are known beforehand). The first two are general purpose implementations where redundant (carry-save) or nonredundant arithmetic can be used, whereas the last one is a simplification of the first two. The proposed architectures present a good trade-off between latency and hardware complexity when compared with existing CORDIC architectures.